2008
DOI: 10.1177/1559827607311514
|View full text |Cite
|
Sign up to set email alerts
|

State of the Art Reviews: Glycemic Index, Obesity, and Chronic Disease

Abstract: There is increasing evidence that both the amount and type of carbohydrate play an important role in weight management and risk of chronic disease. Classifying carbohydrates according to their post-prandial glycemic effect (ie, the glycemic index of foods) has yielded more useful insights than the historical distinctions of simple versus complex chemical structure. Diets based on carbohydrate foods that are more slowly digested and absorbed (ie, low glycemic index diets) have been independently linked to reduc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2009
2009
2017
2017

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(10 citation statements)
references
References 120 publications
0
10
0
Order By: Relevance
“…Subsequent research has confirmed those findings and generated strong evidence from meta-analysis and meta-regression studies demonstrating that low GI diets are linked to improved risk markers for prevention of type II diabetes and its comorbidities (Barclay et al 2008;Brand-Miller et al 2003;Halton et al 2008;Livesey et al 2008;Marsh and BrandMiller 2008;Opperman et al 2004;Wolever and Mehling 2002). Lower GI foods and diets provoke only transient, moderate postprandial glycaemia and improve insulin sensitivity along with other endpoints of cardio-metabolic health in obese and overweight subjects as well as those with type II diabetes (Brand-Miller et al 2003;Dickinson and Brand-Miller 2005;Livesey et al 2008;Marsh and Brand-Miller 2008;Opperman et al 2004;Wolever and Mehling 2002). Furthermore, low GI diets improve metabolic health indices independent of the amount of carbohydrate consumed (Psaltopoulou et al 2010).…”
Section: Introductionmentioning
confidence: 75%
See 1 more Smart Citation
“…Subsequent research has confirmed those findings and generated strong evidence from meta-analysis and meta-regression studies demonstrating that low GI diets are linked to improved risk markers for prevention of type II diabetes and its comorbidities (Barclay et al 2008;Brand-Miller et al 2003;Halton et al 2008;Livesey et al 2008;Marsh and BrandMiller 2008;Opperman et al 2004;Wolever and Mehling 2002). Lower GI foods and diets provoke only transient, moderate postprandial glycaemia and improve insulin sensitivity along with other endpoints of cardio-metabolic health in obese and overweight subjects as well as those with type II diabetes (Brand-Miller et al 2003;Dickinson and Brand-Miller 2005;Livesey et al 2008;Marsh and Brand-Miller 2008;Opperman et al 2004;Wolever and Mehling 2002). Furthermore, low GI diets improve metabolic health indices independent of the amount of carbohydrate consumed (Psaltopoulou et al 2010).…”
Section: Introductionmentioning
confidence: 75%
“…Diet is implicated in the onset and progression of these health problems and carbohydrate quality is a strong predictor of disease risk. Choosing to eat foods with predominately slowly digestible carbohydrates has been shown to be linked to favourable health outcomes including reduced risk of type II diabetes and related conditions (Barclay et al 2008;Halton et al 2008;Livesey et al 2008;Marsh and Brand-Miller 2008).…”
Section: Gi (In Vivo)mentioning
confidence: 99%
“…For adult men and women, an increase in GL above ;100 to 120 g/d increases the risk of diabetes, coronary heart disease (CHD), and possibly certain cancers (16)(17)(18). Again, this is not a problem developing from the metabolic effects of the lowglycemic fructose (19) component of the diet.…”
Section: A Classification Of Fructose Intakesmentioning
confidence: 96%
“…O besity prevalence, morbidity and mortality rates have significantly increased worldwide (1,2). In 2005, World Health Organization (WHO) estimated an overweight and obesity prevalence of 60% and 20-30%, respectively (1).…”
Section: Introductionmentioning
confidence: 99%
“…However, diet is still the major therapeutic base against this disease (3). The results of several studies indicate a positive association between the consumption of high glycemic index (GI) diets versus obesity and related diseases manifestation (2,3).…”
Section: Introductionmentioning
confidence: 99%